Study the Relationship of Executive Functions with Behavioral Symptoms in Children with High-Functioning Autism - Vali Shiri; Seyyed Ali Hosseini; Ebrahim Pishyareh; Vahid Nejati; Akbar Biglarian (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: The relation between autism disorder’s symptoms and cognitive capabilities can help with a better phenotype description of this disorder and can facilitate its pathological evaluation and treatment. Destruction of executive functions seems to be one of the cognitive reasons of potential phenotype in autism disorder. Thus, the present paper aims to study the relationship between executive dysfunction and autism disorder’s symptoms. Materials & Methods: In this cross-sectional research, 50 children with high-functioning autism were selected using convenience sampling method from Behara, Tehranpars and Roshd centers. Then, the GARS test and Autism Spectrum Screening Questionnaire was completed by therapists and neuropsychological tests of Strop and continuous performance test and shift attention were taken by the subjects. Pearson correlation coefficient and multi-variant regression were used for data analysis. Results: There is a significant positive relationship between selective attention with communicative and social interaction symptoms, sustained attention with social interaction symptoms and repetitive behaviors, shifting attention with communicative, social interaction and repetitive behavior symptoms (P<0.001) (P<0.01) (P<0.05). In addition, the results of regression analysis also revealed that selective attention and shifting attention can predict communication, and sustained attention can predict social interaction and repetitive behaviors symptoms (P<0.01) (P<0.05). Conclusion: The results obtained by this study indicate the significant role of executive functions in autistic symptoms. Thus, it is recommended to consider new treatment interventions in repairing executive functions for treatment of children with autistic disorder.